Tungsten carbide powder

By adding chromium on the surface of tungsten carbide grains, improving its affinity with cobalt, and performing two-stage firing, the problems of cemented carbide generation efficiency and densification in the prior art are solved, and strength and high efficiency are achieved carbide generation.

CN119278183APending Publication Date: 2025-01-07KYOCERA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046473.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art still has room for improvement in the efficient generation of cemented carbide powders generated by recycling technology, especially in the liquid phase occurrence temperature range and crystal densification of cobalt.

Method used

By increasing the secondary ionic strength of chromium from the surface of the tungsten carbide grains to the depth direction 5nm area, the strength ratio between chromium and tungsten is increased, and the affinity of cobalt and tungsten carbide powder is enhanced, and the affinity of cobalt and tungsten carbide powder is enhanced, and the low temperature burning is carried out. The formation and sintering are carried out in two stages to form a mixed structure of coarse particles and fine particles, reducing the uneven distribution of chromium at the grain boundary.

Benefits of technology

The efficient generation of low-temperature sintered cemented carbide is achieved, reducing the deformation amount, and forming a strong and efficient cemented carbide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278183A_ABST
    Figure CN119278183A_ABST
Patent Text Reader

Abstract

The tungsten carbide powder contains a powder having tungsten carbide crystal grains as a main component. Furthermore, the strength ratio (Cr / W) of the secondary ion strength (Cr) of chromium to the secondary ion strength (W) of tungsten is 1.0 or more when analysis is performed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) in a region from the outermost surface of the tungsten carbide crystal grains up to 5 (nm) in the depth direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to tungsten carbide powder. Background Art

[0002] In recent years, the development of recycling technology for metals or metal compounds has been promoted. For example, tungsten carbide is a component of super-hard alloys such as cemented carbide, and is used together with cobalt, niobium, etc., and is often used in cutting tools.

[0003] In addition, the metal tungsten contained in tungsten carbide has a high melting point and is therefore used in various applications such as heating elements, structural components, catalysts for the petrochemical industry, environmental equipment, wiring of ceramic wiring boards, and heat dissipation components. In order to effectively utilize these resources, a method for recycling tungsten from scrap has been devised (see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-2927 Summary of the invention

[0007] The tungsten carbide powder of the present invention comprises a powder having tungsten carbide grains as a main component. In addition, in the region from the outermost surface to 5 (nm) in the depth direction of the tungsten carbide grains, when analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) is greater than 1.0. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 It is a diagram showing the structure of tungsten carbide grains according to the embodiment.

[0009] Figure 2 This is a flowchart showing an example of the procedure of the step of producing tungsten carbide according to the embodiment.

[0010] Figure 3 This is a flowchart showing an example of the procedure of a process for producing tungsten carbide according to a reference example.

[0011] Figure 4 This is a diagram showing the depth-direction distribution of the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) in the tungsten carbide powder. DETAILED DESCRIPTION

[0012] Hereinafter, embodiments of the tungsten carbide powder disclosed in the present invention will be described with reference to the drawings. Note that the present invention is not limited to the embodiments described below.

[0013] In recent years, the development of recycling technology for metals or metal compounds has been promoted. For example, tungsten carbide is a component of super-hard alloys such as cemented carbide, and is used together with cobalt, niobium, etc., and is often used in cutting tools.

[0014] In addition, since the metal tungsten contained in tungsten carbide has a high melting point, it is used in various applications such as heating elements, structural components, catalysts for the petrochemical industry, environmental equipment, wiring of ceramic wiring boards, and heat dissipation components. In order to effectively utilize these resources, methods for recycling tungsten from scrap have been designed.

[0015] On the other hand, in the above-mentioned prior art, when using tungsten carbide powder generated by recycling technology, there is still room for further improvement in efficiently generating cemented carbide. Therefore, it is expected to realize a technology that can solve the above-mentioned problems and efficiently generate cemented carbide.

[0016] The tungsten carbide powder of the embodiment comprises tungsten carbide grains 1 (refer to Figure 1 ) as a main component. For example, the tungsten carbide powder of the embodiment includes a powder containing tungsten carbide grains 1 and inevitable impurities.

[0017] Furthermore, in the embodiment, the outermost surface 1a (refer to Figure 1 ) to 5 (nm) in the depth direction, when analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) can be greater than 1.0.

[0018] As described above, since a large amount of chromium having high solubility in cobalt exists on the surface of the tungsten carbide powder, the affinity (wettability) of cobalt used as a binder material of the cemented carbide with the tungsten carbide powder is improved.

[0019] Thus, when the mixed powder of tungsten carbide powder and cobalt powder is fired to produce cemented carbide, cobalt that has liquefied in the temperature range where the liquid phase of cobalt begins to appear smoothly wets and spreads on the surface of the tungsten carbide powder containing a large amount of chromium.

[0020] Therefore, according to the embodiment, cemented carbide can be produced by low temperature sintering, so cemented carbide can be produced efficiently. In addition, in the embodiment, since the crystals are perfectly densified when cemented carbide is produced, cemented carbide with little deformation can be obtained.

[0021] In the embodiment, in the region from the outermost surface 1 a to 5 (nm) in the depth direction of the tungsten carbide grain 1 , when analyzed by TOF-SIMS, the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) may be 1.3 or more.

[0022] Therefore, when the mixed powder of tungsten carbide powder and cobalt powder is fired to produce cemented carbide, cobalt that has liquefied in the temperature range where the liquid phase of cobalt begins to appear wets and spreads more smoothly on the surface of the tungsten carbide powder containing a large amount of chromium.

[0023] Therefore, according to the embodiment, cemented carbide can be produced more efficiently. In addition, according to the embodiment, cemented carbide with a smaller deformation amount can be obtained.

[0024] Figure 1 1 is a diagram showing the structure of a tungsten carbide grain 1 according to an embodiment. Figure 1 As shown, the powder having tungsten carbide grains 1 as a main component includes a combination 2 having a plurality of tungsten carbide grains 1 .

[0025] Furthermore, in the embodiment, the atomic ratio of chromium in the grain boundaries 1 b of the plurality of tungsten carbide grains 1 in the bonded body 2 may be 1 (at %) or less.

[0026] By reducing the uneven distribution of chromium at the grain boundaries 1b in this way, a mixed structure of coarse and fine particles can be easily formed when the mixed powder is heated to 1400 (°C) to 1600 (°C) and sintered in two stages in the cemented carbide manufacturing process. The reason is as follows.

[0027] The tungsten carbide grains 1 have a property that grain growth is reduced at locations with a high chromium content. However, since there is no segregation of chromium at the grain boundaries 1 b of the tungsten carbide grains 1 , the grain boundaries 1 b are likely to become starting points for grain growth.

[0028] On the other hand, the outermost surface 1 a of the tungsten carbide grain 1 has a relatively high chromium content as described above, and therefore is unlikely to serve as a starting point for grain growth.

[0029] Thus, in the embodiment, by mixing positions that are easy to become the starting point of grain growth and positions that are difficult to become the starting point of grain growth in the binder 2, it is easy to form a mixed structure of coarse particles and fine particles when the mixed powder of tungsten carbide powder and cobalt powder is sintered to generate cemented carbide.

[0030] That is, in the embodiment, since the uneven distribution of chromium is reduced in the grain boundaries 1 b, a mixed structure of coarse grains and fine grains is easily formed, and thus a tough cemented carbide can be produced.

[0031] Example

[0032] Hereinafter, embodiments of the present invention will be described in detail. Figure 2 FIG. 1 is a flow chart showing an example of the steps of a process for producing tungsten carbide powder according to an embodiment. Figure 2 As shown, in the step of producing tungsten carbide powder according to the embodiment, first, scrap cemented carbide is prepared.

[0033] Cemented carbide, a type of super-hard alloy, is mainly composed of composite carbides such as metal tungsten and tungsten carbide, with iron, nickel, cobalt, etc. as a binder phase, and contains TiC, TaC, NbC, VC, Cr3C2, etc. as additives as needed.

[0034] Examples of target hard alloy-containing materials to be processed include cutting tools (cutting inserts, drills, end mills, etc.), dies (forming rollers, forming dies, etc.), civil engineering and mining tools (oil drilling tools, rock crushing tools, etc.), and the like.

[0035] Next, the prepared cemented carbide scrap is oxidized and roasted to obtain a mixture of tungsten oxide (WO3) and cobalt tungstate (CoWO4). The mixture is then refluxed with an aqueous sodium hydroxide (NaOH) solution and extracted to obtain a tungsten compound solution containing sodium tungstate (Na2WO4).

[0036] Next, an adsorbent containing lysine is added to the obtained tungsten compound solution, so that the tungsten compound ions are adsorbed on lysine (expressed as lysine-WO4 in the figure).

[0037] In addition, the adsorbent in the present invention is not limited to containing lysine, but may also contain at least one first amino acid selected from alanine, cystine, methionine, tyrosine, valine, glutamic acid, histidine, proline, threonine, asparagine, glycine, isoleucine, ornithine, arginine, serine, citrulline and cystathionine.

[0038] In such adsorption treatment, for example, the total amount of the first amino acid salt added to the adsorbent is 0.2 (mol) to 1.1 (mol) per 1 (mol) of the metal component of the tungsten compound. Thus, a large amount of tungsten compound can be adsorbed by a small amount of adsorbent.

[0039] In addition, the total amount of the salt of the first amino acid added is, for example, 10 (g / l) to 300 (g / l) relative to the tungsten compound solution. As a result, the viscosity of the solution does not increase, and the recovery efficiency of the metal compound is unlikely to decrease. In particular, when the adsorbent contains a salt of an amino acid, the viscosity of the solution is unlikely to increase, and the operability is good.

[0040] The temperature can be adjusted according to the activity of the free amino acid, and can usually be room temperature. The tungsten compound solution to which the adsorbent is added can be adjusted using hydrochloric acid or the like so that the zeta potential of the free amino acid is positive. Thus, the tungsten compound ions as anions can be adsorbed on the adsorbent.

[0041] In addition, the pH of the solution may be lower than 7 (acidic). When the free amino acid is lysine or arginine, the appropriate pH is 4 or lower, preferably 0.5 to 3.0, and preferably pH = 0.8 to 2.3. When the free amino acid is glutamic acid, the appropriate pH is 1.5 or lower.

[0042] This can improve the recovery rate of the tungsten compound. Note that either the step of adjusting the pH of the solution or the step of adding the adsorbent to the solution containing the metal compound may be performed first.

[0043] When the adsorbent is a salt of the first amino acid, the recovery efficiency of the adsorbent is high if the adsorption reaction is within 1 hour. That is, if the adsorption reaction exceeds 1 hour, part of the adsorbed metal compound may be separated from the free amino acid.

[0044] Next, in the lysine adsorption step, the adsorbent on which the tungsten compound ions are adsorbed is filtered out by means of a filter or the like.

[0045] Next, the adsorbent after filtration is washed in the order of acid washing and pure water washing as needed. In addition, the adsorbent after filtration can be washed with warm water above 40 (°C) instead of acid washing. In addition, pure water washing is performed to remove impurities until the conductivity of the washing filtrate is below 500 (μS / m). In this way, the tungsten compound can be high-graded and recovered.

[0046] Next, the washed adsorbent is squeezed by a press or the like. A necessary amount of chromium acetate powder is added to the squeezed adsorbent. The amount of chromium acetate powder added is preferably 0.4 (wt%) to 20.0 (wt%) relative to the dry weight of the tungsten-containing adsorbent, for example.

[0047] In addition, the water absorption rate of the squeezed adsorbent is preferably 40% or more. Thus, by making the adsorbent contain a large amount of water, the chromium acetate powder added to the squeezed adsorbent can be well dissolved in the adsorbent.

[0048] Next, the adsorbent having adsorbed tungsten compound ions is dried and further incinerated at a temperature of 300° C. or higher in the air, for example, to oxidize the tungsten compound and remove organic components including the adsorbent and additives, thereby obtaining tungsten oxide powder (WO 3 ).

[0049] Next, the obtained tungsten oxide powder is heat-treated in a reducing atmosphere (for example, a hydrogen atmosphere) at a temperature of 800 (°C) to 950 (°C) to reduce the tungsten oxide compound. Thus, metal tungsten (W) can be obtained. Finally, the obtained metal tungsten is carbonized to obtain the tungsten carbide powder (WC) of the embodiment.

[0050] Figure 3 FIG. 1 is a flow chart showing an example of the steps of the process of producing tungsten carbide powder according to the reference example. Figure 3 As shown, in the step of producing tungsten carbide powder of the reference example, first, scrap cemented carbide is prepared.

[0051] Next, the prepared cemented carbide scrap is oxidized and roasted to obtain a mixture of tungsten oxide (WO3) and cobalt tungstate (CoWO4). Then, the obtained mixture is extracted with an aqueous sodium hydroxide (NaOH) solution to obtain a tungsten compound solution containing sodium tungstate (Na2WO4). Each step so far is the same as the above-mentioned embodiment, so the detailed description is omitted.

[0052] Next, the obtained tungsten compound solution is subjected to ion exchange with an ion exchange resin or the like to generate an aqueous solution of ammonium tungstate ((NH4)2WO4). The obtained aqueous solution is then heated and concentrated to crystallize the tungsten compound as ammonium paratungstate (APT).

[0053] Next, the obtained APT is thermally decomposed to oxidize the APT, thereby obtaining tungsten oxide powder (WO 3 ).

[0054] Next, the obtained tungsten oxide powder is heat-treated in a reducing atmosphere to reduce the tungsten oxide compound, thereby obtaining metal tungsten (W). Finally, the obtained metal tungsten is carbonized to obtain tungsten carbide powder (WC) of the reference example.

[0055] Next, the obtained tungsten carbide powders of the embodiment and the reference example were analyzed by TOF-SIMS (Time-Of-Flight Secondary Ion Mass Spectrometry). Specifically, the depth distribution of tungsten and chromium in the tungsten carbide powders of the embodiment and the reference example was measured by TOF-SIMS.

[0056] The measurement conditions of TOF-SIMS are as follows. The tungsten carbide powders of the embodiment and the reference example are fixed, and the powder surface is measured in a 100 (μm) square. In addition, the measurement device is TOF.SIMS5 of ION-TOF Company, and Bi (bismuth) is selected as the primary ion source to measure the elemental analysis in the depth direction.

[0057] In addition, elemental analysis in the depth direction was performed on samples 1 and 2 of the tungsten carbide powder of the embodiment and samples 3 and 4 of the tungsten carbide powder of the reference example. Then, the depth distribution of the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) was obtained for each sample.

[0058] Figure 4 This is a diagram showing the depth-direction distribution of the intensity ratio (Cr / W) of the secondary ion intensity of chromium (Cr) to the secondary ion intensity of tungsten (W) in the tungsten carbide powder.

[0059] like Figure 4 As shown in the figure, in the tungsten carbide powder (samples 1 and 2) of the embodiment, the outermost surface 1a (refer to Figure 1 ) to 5 (nm) in the depth direction, the intensity ratio (Cr / W) is greater than 1.0.

[0060] On the other hand, it can be seen that in the tungsten carbide powder of the reference example (samples 3 and 4), the outermost surface 1a (reference Figure 1 In at least a portion of the region from ) to 5 (nm) in the depth direction, the intensity ratio (Cr / W) is not greater than 1.0.

[0061] Thus, in the embodiment, by increasing the chromium concentration of the outermost surface 1a and the vicinity of the tungsten carbide grains 1, as described above, cemented carbide can be efficiently generated. In addition, in the embodiment, by increasing the chromium concentration of the outermost surface 1a and the vicinity of the tungsten carbide grains 1, cemented carbide with less deformation can be obtained.

[0062] In addition, if Figure 4 As shown in the figure, in the tungsten carbide powder (samples 1 and 2) of the embodiment, the outermost surface 1a (refer to Figure 1 ) in the entire region from 5 (nm) in the depth direction, the intensity ratio (Cr / W) is greater than 1.3.

[0063] On the other hand, it can be seen that in the tungsten carbide powder of the reference example (samples 3 and 4), the outermost surface 1a (reference Figure 1 In at least a portion of the region from ) to 5 (nm) in the depth direction, the intensity ratio (Cr / W) is not greater than 1.3.

[0064] Thus, in the embodiment, by further increasing the chromium concentration of the outermost surface 1a and the vicinity of the tungsten carbide grains 1, as described above, cemented carbide can be generated more efficiently. In addition, in the embodiment, by further increasing the chromium concentration of the outermost surface 1a and the vicinity of the tungsten carbide grains 1, cemented carbide with less deformation can be obtained.

[0065] In the obtained tungsten carbide powder bond 2 of the embodiment, the atomic ratios of various elements in the tungsten carbide crystal grains 1 and the atomic ratios of various elements in the grain boundaries 1 b were measured by STEM (Scanning Transmission Electron Microscope).

[0066] Specifically, STEM was used to measure two locations inside the tungsten carbide grain 1 and three locations on the grain boundary 1 b of the tungsten carbide grain 1 to obtain the average atomic ratios of various elements inside the grain and at the grain boundary 1 b.

[0067] The measurement conditions of STEM are as follows. First, as a pretreatment of the sample, the sample was thinned by the FIB method (μ-sampling method). Then, the thinned sample was observed by STEM using a scanning transmission electron microscope (JEM-ARM200F manufactured by JEOL Ltd.). The observation conditions were an acceleration voltage of 200 (kV) and a magnification accuracy of ±10 (%).

[0068] Then, during STEM observation, element analysis (spot analysis) was performed by energy dispersive X-ray spectroscopy (EDX) using an element analysis device (JED-2300T manufactured by JEOL Ltd.) provided in the STEM microscope.

[0069] The analysis conditions are as follows: acceleration voltage of 200 (kV), beam diameter of about 0.1 (nmφ), X-ray detector of Si drift detector, energy resolution of about 140 (eV), X-ray emission angle of 21.9 (°), solid angle of 0.98 (sr), and acquisition time of 60 (seconds). The measurement results of STEM are shown in Table 1.

[0070]

Table 1

[0071]

[0072] As shown in Table 1, in the tungsten carbide powder of the embodiment, the atomic ratio of chromium in the grain boundaries 1 b (described as “grain boundaries” in Table 1) of the plurality of tungsten carbide grains 1 in the binder 2 is 1 (at %) or less.

[0073] Thus, by reducing the uneven distribution of chromium at the grain boundary 1b, as described above, when the mixed powder is heated to 1400 (°C) to 1600 (°C) and sintered in two stages in the manufacturing process of cemented carbide, a mixed structure of coarse particles and fine particles can be easily formed. Therefore, according to the embodiment, a tough cemented carbide can be produced.

[0074] The above is a description of the embodiments of the present invention, but the present invention is not limited to the above embodiments, and various changes can be made as long as they do not deviate from the purpose. For example, in the above embodiments, the case of generating (recycling) tungsten carbide from cemented carbide waste is shown, but the present invention is not limited to this example, and it can also be applied to the case of generating tungsten carbide from ore, etc.

[0075] Further effects and other aspects can be easily derived by those skilled in the art. Therefore, the broader aspects of the present invention are not limited to the specific details and representative embodiments expressed and described above. Therefore, various changes can be made without departing from the spirit or scope of the general concept of the invention as defined by the accompanying claims and their equivalents.

[0076] Description of Reference Numerals

[0077] 1Tungsten carbide grains

[0078] 1a Most superficial

[0079] 1b Grain boundary

[0080] 2 Combination

Claims

1. A tungsten carbide powder, comprising a powder containing tungsten carbide grains as a main component, In the region from the outermost surface to 5 nm in the depth direction of the tungsten carbide grains, when analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the intensity ratio Cr / W of the secondary ion intensity of chromium Cr to the secondary ion intensity of tungsten W is 1.0 or more.

2. The tungsten carbide powder according to claim 1, wherein The intensity ratio Cr / W of the secondary ion intensity Cr of chromium to the secondary ion intensity W of tungsten is 1.3 or more.

3. The tungsten carbide powder according to claim 1 or 2, wherein: The powder comprises a combination of a plurality of tungsten carbide grains. In the grain boundaries of the plurality of tungsten carbide grains in the combined body, the atomic ratio of chromium is 1 at % or less.

Citation Information

Patent Citations

  • Method for processing super hard alloy scrap

    JP2004002927A